The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1074/jbc.ra117.000303
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic mechanism of controlled Fab-arm exchange for the formation of bispecific immunoglobulin G1 antibodies

Abstract: Bispecific antibodies (bsAbs) combine the antigen specificities of two distinct Abs and demonstrate therapeutic promise based on novel mechanisms of action. Among the many platforms for creating bsAbs, controlled Fab-arm exchange (cFAE) has proven useful based on minimal changes to native Ab structure and the simplicity with which bsAbs can be formed from two parental Abs. Despite a published protocol for cFAE and its widespread use in the pharmaceutical industry, the reaction mechanism has not been determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…The pairing consistently allowed for >95% heterodimer formation when parental antibodies were combined with a reducing agent and exchanged. The rate constants have been determined for the mechanism of IgG1 BsAb formation [519].…”
Section: Heavy Chain Heterodimerizationmentioning
confidence: 99%
“…The pairing consistently allowed for >95% heterodimer formation when parental antibodies were combined with a reducing agent and exchanged. The rate constants have been determined for the mechanism of IgG1 BsAb formation [519].…”
Section: Heavy Chain Heterodimerizationmentioning
confidence: 99%
“…The selection of the 30 mg/kg dose used in the studies described earlier was based on pilot studies showing evidence of efficacy at this dose (data not shown). As the biAb (in TBTI format) used in these studies demonstrated lower affinity (due to steric hindrance) to laminin-211 than the parental Ab ( Figure S2 B, left panel), we elected to engineer an improved version based on the Duobody format 29 , 30 (biAb-2) with higher affinities to both laminin-211 and βDG. This biAb-2 was used in a separate dose-response study in LARGE myd-3J mice.…”
Section: Resultsmentioning
confidence: 99%
“…(1) the ease of parental antibody production applying standard IgG production procedures; (2) the opportunity to evaluate affinity, epitope bin, cellular binding, internalization, physico-chemical properties such as thermal stability or hydrophobicity, polyspecificity or self-interaction in IgG format with the same material in advance or in parallel to an HTP screening; (3) the high degree of heterodimerization; (4) the applicability for bsAb, but also biparatopic, ADC screening as reported herein. cFAE has been identified in human IgG4 antibodies [26,[41][42][43], extended to therapeutic bsAb production applying MEA as a reducing agent [25] and extensively studied, including the evaluation of MEA versus DTT or cFAE kinetics [44] and already applied in focused combinatorial screens [27], leading, among others, to the recently approved bispecific antibody amivantamab [4]. Although this is illustrative of an elegant, educated screening cascade based on deep biological knowledge, many novel modes of action necessitate complex and high-throughput screening setups targeting unprecedented biology without an a priori definition of optimal epitope combinations or their respective paratopes.…”
Section: Discussionmentioning
confidence: 99%